Iron phosphate with high specific surface area as well as preparation method and application thereof
By adding inorganic acid and ammonium salt to pre-crystallize and crystallize in the preparation process of iron phosphate, the problems of large size, uneven distribution and low specific surface area in the prior art are solved, and the preparation of iron phosphate with high specific surface area and uniform distribution is achieved, which improves the rate performance of the battery.
Patent Information
- Application Number
- CN202411741838.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The iron phosphate prepared by the existing ammonia process has the problems of large particle size, uneven particle distribution and low specific surface area, which affects the performance of lithium iron phosphate.
By mixing the phosphorus source solution and the iron source solution, an amorphous iron phosphate slurry was obtained. After solid-liquid separation, inorganic acid was added to the slurry re-slurryed by amorphous iron phosphate and water for pre-crystallization, and then an ammonium salt was added for crystallization. After solid-liquid separation, washing, drying and dehydration treatment, iron phosphate with a high specific surface area was obtained.
Iron phosphate with a specific surface area greater than 8.5m2/g was achieved, with uniform particle distribution and good crystallinity, suitable for industrial mass production, and improved the rate performance of the battery.
Smart Images

Figure CN119706766A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and in particular relates to iron phosphate and a preparation method and application thereof. Background Art
[0002] Among the positive electrode materials of lithium-ion batteries, lithium iron phosphate has become a hot research topic for positive electrode materials of lithium-ion batteries due to its advantages of non-toxicity, low price and good safety. With the development of new energy power generation and energy storage, household energy storage and other usage scenarios, the cost and long cycle performance advantages of lithium iron phosphate have become more prominent, and it is widely used in automobiles and large-scale energy storage applications. The particles and morphology of iron phosphate play a vital role in the performance of lithium iron phosphate. The iron phosphate prepared by the existing ammonia process has the disadvantages of large particle size, uneven particle distribution and low specific surface area, while the particle size and specific surface area of iron phosphate directly affect the specific surface area of lithium iron phosphate. The specific surface area of the positive electrode material affects the energy density, rate and cycle performance of the battery. The positive electrode material with a large specific surface area makes the battery have better rate characteristics. Therefore, the study of iron phosphate with uniform particle distribution and high specific surface area and its preparation process has high application value and research significance. Summary of the invention
[0003] In view of the problems existing in the prior art, the main purpose of the present invention is to provide an iron phosphate with a high specific surface area and a preparation method thereof.
[0004] To achieve the above objectives, the present invention provides the following specific technical solutions.
[0005] First, the present invention provides an iron phosphate with a high specific surface area, wherein the specific surface area of the iron phosphate is greater than 8.5 m 2 / g, the primary particle size is 50~150nm, and the secondary particles are in the shape of sticky rods or flakes.
[0006] In a further preferred embodiment, the crystallinity of the iron phosphate is 60-90%.
[0007] Secondly, the present invention provides a method for preparing iron phosphate with a high specific surface area, comprising: The phosphorus source solution and the iron source solution are mixed and reacted to obtain an amorphous iron phosphate slurry; performing solid-liquid separation on the amorphous ferric phosphate slurry to obtain amorphous ferric phosphate; In the slurry prepared by re-slurrying amorphous iron phosphate and water, an inorganic acid is first added to perform pre-crystallization, and then an ammonium salt is added to perform crystallization; The crystallized slurry is subjected to solid-liquid separation treatment, and the obtained solid phase is subjected to washing, drying and dehydration treatment to obtain iron phosphate with a high specific surface area.
[0008] In a further preferred embodiment, the phosphorus source is at least one of phosphoric acid, monoammonium phosphate, diammonium phosphate, and diammonium hydrogen phosphate.
[0009] In a further preferred embodiment, the iron source is at least one of ferrous sulfate, ferrous nitrate, iron powder, ferric chloride, and ferric oxide.
[0010] In a further preferred embodiment, the reaction temperature is 25-65° C. and the pH value is 1.4-2.2.
[0011] In a further preferred embodiment, the inorganic acid is one or both of phosphoric acid and sulfuric acid.
[0012] In a further preferred embodiment, an inorganic acid is added to the re-slurry of amorphous ferric phosphate and water to adjust the pH value of the system to 1.3-1.8.
[0013] In a further preferred embodiment, after adding the inorganic acid, the system is heated to 65° C. to 85° C. for pre-crystallization.
[0014] In a further preferred embodiment, the ammonium salt is at least one of ammonium sulfate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate.
[0015] In a further preferred embodiment, the ammonium salt is ammonium sulfate; the amount of ammonium sulfate solution added is determined according to the molar ratio of iron in the slurry prepared by re-slurrying ammonium sulfate with amorphous ferric phosphate and water being 0.01-0.1:1.
[0016] In a further preferred embodiment, the temperature for crystallization by adding the ammonium salt is higher than the pre-crystallization temperature but not more than 100°C.
[0017] In a further preferred embodiment, the drying temperature is 60-180°C.
[0018] In a further preferred embodiment, the temperature of the dehydration treatment is 400-580°C.
[0019] Based on the same inventive concept, the present invention provides a lithium iron phosphate prepared by using the aforementioned high specific surface area iron phosphate.
[0020] The present invention also provides a battery, wherein the battery comprises the above-mentioned lithium iron phosphate.
[0021] The above one or more technical solutions of the present invention can achieve at least one of the following beneficial effects: The iron phosphate provided by the present invention has small primary particles, uniform particle distribution and high specific surface area, which is conducive to obtaining lithium iron phosphate with a high specific surface area.
[0022] The iron phosphate provided by the present invention has a high specific surface area, good crystallinity and stable crystal form, and can ensure the stability of the lithium iron phosphate structure obtained in subsequent production.
[0023] The method for preparing high specific surface area ferric phosphate of the present invention is suitable for industrial mass production, has simple operation, and has strong adaptability to existing equipment and production lines.
[0024] The lithium iron phosphate prepared from the iron phosphate provided by the present invention is beneficial to improving the rate performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figures 1 to 6 They are SEM images of the iron phosphate obtained in Examples 1 to 6 respectively.
[0026] Figures 7 to 11 They are SEM images of the iron phosphate obtained in Comparative Examples 1 to 5 respectively.
[0027] Figures 12 to 15 They are SEM images of the iron phosphate obtained in Examples 7 to 10 respectively. DETAILED DESCRIPTION
[0028] Some embodiments of the present invention provide iron phosphate with a high specific surface area, wherein the specific surface area of the iron phosphate is greater than 8.5 m 2 / g, the primary particle size is 50~150nm, and the secondary particles are in the shape of sticky rods or flakes.
[0029] Iron phosphate has a high specific surface area, and lithium iron phosphate prepared using it as a precursor material also has a high specific surface area. High specific surface area lithium iron phosphate materials improve the energy density, rate performance and cycle performance of batteries.
[0030] The smaller the particle size of the primary particles of iron phosphate, the higher the grinding efficiency when preparing lithium iron phosphate; at the same time, the smaller the primary particles of iron phosphate, the smaller the primary particles of lithium iron phosphate prepared using it as a precursor material will also be. When the battery is working, the lithium ion transmission path becomes shorter, thereby improving the ion transmission efficiency, which is beneficial to enhancing the battery rate performance and low temperature performance.
[0031] In some specific embodiments of the present invention, the crystallinity of the iron phosphate is 60-90%. The higher the crystallinity, the more stable the crystal form of the iron phosphate will be, and the structure of the obtained lithium iron phosphate will also be more stable. The specific surface area of the iron phosphate provided by the present invention is greater than 8.5 m 2 / g, and the crystallinity is 60~90%. Taking both specific surface area and crystallinity into consideration, the obtained product has better performance.
[0032] At present, the production process of iron phosphate is mainly based on a two-step method. First, the phosphorus source and the trivalent iron source are neutralized to generate amorphous iron phosphate with low crystallinity and spherical primary particles. Then phosphoric acid is added for crystal transformation, and excess impurities are removed to form dihydrate iron phosphate. Finally, it is dehydrated to form anhydrous iron phosphate. The primary particles are spherical, but during the sintering process, the primary particles will agglomerate to form porous agglomerates without specific morphology. This process usually causes serious agglomeration of materials, large particles, low specific surface area, and difficulty in subsequent crushing. In addition, there are methods of using surfactants in the crystallization process to inhibit the agglomeration between particles and thus improve the specific surface area. There are also studies on improving the specific surface area by forming porous iron phosphate by artificial pores. However, the introduction of surfactants affects the subsequent sewage treatment, and the artificial pore method is difficult to mass produce.
[0033] The commonly used process for synthesizing iron phosphate is to first generate amorphous iron phosphate yellow material and then add phosphoric acid for crystallization. Since phosphoric acid itself has a high viscosity, with the continuous addition of phosphate ions, the viscosity of the crystallization slurry gradually increases, making the dispersion of the generated iron phosphate crystal nuclei worse, and the iron phosphate grains aggregate and become larger, which easily generates iron phosphate with large primary particles, uneven distribution and low specific surface area.
[0034] In order to solve the above defects, the present invention proposes the following specific technical solutions.
[0035] Some embodiments of the present invention provide a method for preparing iron phosphate with a high specific surface area, comprising: The phosphorus source solution and the iron source solution are mixed and reacted to obtain an amorphous iron phosphate slurry; performing solid-liquid separation on the amorphous ferric phosphate slurry to obtain amorphous ferric phosphate; In the slurry prepared by re-slurrying amorphous iron phosphate and water, an inorganic acid is first added to perform pre-crystallization, and then an ammonium salt is added to perform crystallization; The crystallized slurry is subjected to solid-liquid separation treatment, and the obtained solid phase is subjected to washing, drying and dehydration treatment to obtain iron phosphate with a high specific surface area.
[0036] Phosphoric acid is added first during crystallization, and then ammonium salt is added. Phosphoric acid is first adsorbed on the surface of amorphous particles, and then the addition of ammonium salt makes ammonium ions and iron complexed between amorphous particles. The ammonium salt is at least one of ammonium sulfate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate. Ammonium sulfate is preferably used. The sulfate ions in ammonium sulfate can replace part of the phosphate ions, reduce the iron-phosphorus ratio, and reduce the aggregation between particles. During the dehydration process, sulfate and ammonium ions will be taken off by the burning gas, and the space left will increase the specific surface area of ferric phosphate, and the positive pressure of the gas can play a role in pore formation, reducing the aggregation between particles, thereby obtaining ferric phosphate with small primary particles, uniform particle distribution, and high specific surface area.
[0037] In some specific embodiments, the phosphorus source is at least one of phosphoric acid, monoammonium phosphate, diammonium phosphate, and diammonium hydrogen phosphate. Those skilled in the art may also select other phosphorus sources for synthesizing iron phosphate in the art.
[0038] In some specific embodiments, the iron source is at least one of ferrous sulfate, ferrous nitrate, iron powder, ferric chloride, and ferric oxide. Those skilled in the art may also select other iron sources for synthesizing ferric phosphate in the art.
[0039] The concentrations of the phosphorus source solution and the iron source solution can be selected at conventional concentrations, for example, 3% to 7% of the phosphorus source solution and 4% to 7% of the iron source solution.
[0040] In some specific embodiments, the reaction temperature is 25-50°C, and the pH value is 1.5-2.1. When the reaction temperature increases, the movement rate of molecules or ions in the reaction system will be accelerated, and various materials can be mixed more evenly. However, when the synthesis temperature is too high, the activation energy of the surface of the synthesized amorphous iron phosphate particles will increase, and the particles will be more likely to agglomerate, which is not conducive to the uniform growth of particles; and when the temperature is too high and the time is too long, the synthesized amorphous iron phosphate will directly transform into crystalline iron phosphate, and the impurity content of the obtained iron phosphate is relatively high.
[0041] In some specific embodiments, the inorganic acid is one or both of phosphoric acid and sulfuric acid.
[0042] In some specific embodiments, the ammonium salt is at least one of ammonium sulfate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate, and more preferably ammonium sulfate.
[0043] In some specific embodiments, an inorganic acid is added to the slurry of amorphous ferric phosphate and water to make the pH value of the system 1.3-1.8. As the pH value decreases, the supersaturation of the system increases, the rate of crystal nucleation increases, and the growth rate of the crystal nucleus is slow, and the particle size of the obtained product is small; if the pH value of the system is too low, part of the generated amorphous ferric phosphate will be dissolved, increasing the loss of iron and phosphorus; if the pH value is too high, the supersaturation of the system will decrease, the rate of crystal nucleation will be reduced, the particle size of the obtained product will be large, and basic ferric phosphate or part of ferric hydroxide will be generated, and the impurity level of the obtained ferric phosphate product is poor.
[0044] In some specific embodiments, the time for adding the inorganic acid is greater than 10 minutes, and then the system is heated to 65-85°C for pre-crystallization. If the time for adding the inorganic acid is too short, there may be uneven bonding between the phosphate and the amorphous iron phosphate; the heating here is to promote the reaction between the phosphate and the amorphous iron phosphate particles for pre-crystallization, but the temperature should not be too high, otherwise the slurry will crystallize and turn white; ammonium sulfate is added before the slurry turns white and crystallizes.
[0045] In some specific embodiments, the amount of ammonium sulfate added is determined based on the molar ratio of iron in the slurry re-slurried by ammonium sulfate, amorphous iron phosphate and water, which is 0.01~0.1:1. As the amount of ammonium sulfate added increases, the viscosity of the slurry will increase. After excessive addition of ammonium sulfate, the dispersibility of amorphous iron phosphate in the slurry is affected by the viscosity, resulting in serious particle aggregation, which affects the reformation of the crystal structure of iron phosphate during the crystallization process. The crystallization process cannot turn white normally, the product surface has serious adhesion / fusion phenomenon, the specific surface area is reduced, and the crystallinity is greatly reduced, and the stability of the crystal structure is poor. In some embodiments of the present invention, by controlling the amount of ammonium sulfate added, the specific surface area and crystallinity of the iron phosphate obtained reach a relatively balanced state.
[0046] In some specific embodiments, the temperature for adding ammonium sulfate for crystallization is higher than the pre-crystallization temperature, but not higher than 100° C. When the crystallization temperature is too low, the movement rate of molecules or ions in the system is very slow, the average kinetic energy is small, the crystallization whitening time is long, the crystal nuclei are formed slowly and in small numbers, resulting in large crystal particle size.
[0047] In some specific embodiments, the drying temperature is 60-180°C.
[0048] In some specific embodiments, the temperature of the dehydration treatment is 400-580° C. The dehydration temperature should ensure the control of the water content in the ferric phosphate, and on the other hand, the temperature of the dehydration treatment should be conducive to the formation of sulfur dioxide and ammonia gas from sulfate and ammonium ions.
[0049] In addition, the present invention also provides lithium iron phosphate prepared by the aforementioned iron phosphate, and a battery using the obtained lithium iron phosphate material as a positive electrode active material.
[0050] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0051] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0052] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0053] Example 1 (1) Ingredients: Weigh 59.26 g of monoammonium phosphate into a beaker, add 166.41 g of water, stir to dissolve, and prepare a monoammonium phosphate solution with a phosphorus content of 7%; weigh 700 g of ferrous sulfate solid, add 800 g of deionized water, stir for 10 min to pre-dissolve, then add 5% of the total weight of the system concentrated sulfuric acid to prepare a solution with an iron concentration of about 7%, and then add 43.27 g of 25% concentration hydrogen peroxide for oxidation to obtain a ferric sulfate solution.
[0054] (2) Synthesis: Add 50g of water as the base liquid to the flask, start rapid stirring, and the stirring frequency is 1200r / min. Add ferric sulfate solution, monoammonium phosphate solution and ammonia water to the flask in parallel through a peristaltic pump, control the feeding time to be 30min, the synthesis temperature to be 45℃, the pH value to be 1.8, and then continue to stir and react for 30min; after the reaction is completed, a yellow material is obtained. The yellow material is subjected to filter pressing treatment, and the solid phase is washed to obtain the washed yellow material.
[0055] (3) Crystallization: Add water to the washed yellow material to make a slurry and disperse it. Add the dispersed slurry into a flask and start rapid stirring at a frequency of 1200 r / min. Add 5.19 g of phosphoric acid and raise the temperature to 65°C. Continue stirring for 15 minutes, take a sample to measure the pH value and record it. Control the pH value within the range of 1.3-1.8. Then add ammonium sulfate solid in an amount of 0.02 times the molar amount of iron in the slurry, raise the temperature to 85°C, and continue stirring. After the slurry turns white, adjust the stirring frequency to 500 r / min and continue to keep warm and age for three hours. The reaction is complete.
[0056] (4) The aged slurry was filtered, and the cake was washed twice with 750 g of water; the filter cake was placed in an oven and dried at 100° C. for 10 h to obtain dihydrated iron phosphate; the prepared dihydrated iron phosphate was placed in a muffle furnace and dehydrated at 530° C. for 3 h to obtain anhydrous iron phosphate.
[0057] Example 2 The difference between Example 2 and Example 1 is only that: In the crystallization step (3), the amount of ammonium sulfate added is 0.04 times the molar amount of iron in the slurry.
[0058] Example 3 The difference between Example 3 and Example 1 is only that: In the crystallization step (3), the amount of ammonium sulfate added is 0.08 times the molar amount of iron in the slurry.
[0059] Example 4 The difference between Example 4 and Example 1 is only that: In the crystallization step (3), the amount of ammonium sulfate added is 0.10 times the molar amount of iron in the slurry.
[0060] Example 5 The difference between Example 5 and Example 1 is only that: In step (3) the crystallization step, diammonium phosphate is added.
[0061] Example 6 The difference between Example 6 and Example 1 is only that: In step (3) the crystallization step, diammonium hydrogen phosphate is added.
[0062] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is only that: In step (3) the crystallization step, ammonium sulfate was not added.
[0063] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is only that: In the crystallization step (3), the amount of ammonium sulfate added is 0.50 times the molar amount of iron in the slurry.
[0064] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is only that the crystallization step (3) is different, specifically: (3) Crystallization: Add water to the washed yellow material to make a slurry and disperse it again. Add the dispersed slurry into a flask and start rapid stirring at a frequency of 1200 r / min. Then add ammonium sulfate 0.02 times the molar amount of iron in the slurry and stir for 10 min. Add 5.19 g of phosphoric acid and continue stirring for 5 min. Take a sample to measure the pH value and record it. Control the pH value within the range of 1.3-1.8 and continue stirring. Start heating to 85°C. After the slurry turns white, adjust the stirring frequency to 500 r / min and continue to keep warm and age for three hours. The reaction is complete.
[0065] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is only that the crystallization step (3) is different, specifically: (3) Crystallization: Add water to the washed yellow material to make a slurry and disperse it again. Add the dispersed slurry into a flask and start rapid stirring at a frequency of 1200 r / min. Then, add 0.02 times the molar amount of iron in the slurry of ammonium sulfate and 5.19 g of phosphoric acid at the same time. Stir for 5 minutes, take a sample to measure the pH value and record it. Control the pH value within the range of 1.3-1.8. Continue stirring and start heating to 85°C. After the slurry turns white, adjust the stirring frequency to 500 r / min. Continue to keep warm and age for three hours. The reaction is complete.
[0066] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that ammonium sulfate is added during the synthesis of the yellow material. Specifically, step (2) and step (3) are different: (2) Synthesis: Add 50g of water as the base liquid to the flask, start rapid stirring at a frequency of 1200r / min, and then add the same ammonium sulfate as in Example 1. Add the ferric sulfate solution, monoammonium phosphate solution and ammonia water to the flask in parallel through a peristaltic pump, control the feeding time to be 30min, and then continue stirring and reacting for 30min; after the reaction is completed, a yellow material is obtained. The yellow material is subjected to filter pressing treatment, and the solid phase is washed to obtain the washed yellow material.
[0067] (3) Crystallization: Add water to the washed yellow material to make a slurry and disperse it. Add the dispersed slurry into a flask and start rapid stirring at a frequency of 1200 r / min. Then add 5.19 g of phosphoric acid and stir for 5 min. Take a sample to measure the pH value and record it. Control the pH value within the range of 1.3-1.8. Continue stirring and start heating to 85°C. After the slurry turns white, adjust the stirring frequency to 500 r / min and continue to keep warm for 3 hours. The reaction is complete.
[0068] Figure 1-6 The following are SEM images of the iron phosphate obtained in Examples 1-6 respectively.
[0069] Figure 7-11 They are SEM images of the iron phosphate obtained in Comparative Examples 1-5 respectively.
[0070] The particle size of the primary particles of the obtained iron phosphate can be determined based on the SEM image. Since the primary particles are rod-like in shape, the particle size here refers to the longitudinal dimension of the particles.
[0071] The physicochemical characteristics of the obtained iron phosphate were further determined by the following method.
[0072] Specific surface area: GB / T 13390-2008 Determination of specific surface area of metal powder-Nitrogen adsorption method was used, and the specific surface area was tested using a specific surface meter.
[0073] Particle size distribution: Reference HG / T 4701 Iron phosphate for batteries 5.11 particle size determination method; mix the sample, weigh 0.1g sample, put it in a 100mL clean beaker filled with 50mL water, and then ultrasonicate for 15min and use Bettersize2600 laser particle size distribution analyzer wet method system for detection.
[0074] Crystallinity: After the sample is tested by X-ray diffractometer, the XRD spectrum is exported and then processed according to MDI Jade software to obtain crystallinity data.
[0075] pH value: Refer to GB / T 9724-2007 General Rules for Determination of pH Value of Chemical Reagents, weigh 6g of sample, accurately place it in a beaker, add 54g of water, ultrasonicate for 15min, and determine the pH value with a Mettler pH meter.
[0076] The results are shown in Table 1.
[0077] Table 1 No ammonium salt is added during the crystallization process (as shown in Comparative Example 1), and the specific surface area of the obtained iron phosphate is small and the crystallinity is high. When a certain amount of ammonium sulfate / ammonium dihydrogen phosphate / diammonium hydrogen phosphate is added during the crystallization process, the specific surface area of the obtained iron phosphate is greatly improved, but the crystallinity is reduced. And with the increase in the amount of ammonium sulfate added (as shown in Examples 1-4 and Comparative Example 2), the specific surface area and crystallinity of iron phosphate tend to gradually decrease. In other words, the appropriate amount of ammonium salt added is more important for obtaining iron phosphate with both high specific surface area and appropriate crystallinity.
[0078] In the crystallization process, ammonium sulfate is added first, and then phosphoric acid is added (as shown in Comparative Example 3). The specific surface area of the obtained iron phosphate is small, the crystallinity is reduced, and the particle size distribution is uneven. This may be because: when ammonium sulfate is added first, the ammonium ions will directly complex with iron, and the phosphoric acid added later can play a limited role, so that the specific surface area cannot be increased and the particle size is further increased. The SEM image of the iron phosphate obtained in Comparative Example 3 shows that the particles are agglomerated, and the secondary particles are larger.
[0079] When ammonium sulfate and phosphoric acid are added simultaneously during the crystallization process (as shown in Comparative Example 4), the specific surface area of the obtained iron phosphate is also small, the crystallinity does not change much, and the particle size distribution is uneven. This may be because: since phosphoric acid and ammonium sulfate are added to the slurry at the same time, the ammonium radical will react with the iron, and the sulfate radical will also be adsorbed on the surface of the amorphous iron phosphate, so that the binding sites of the phosphate radical and the amorphous iron phosphate are reduced, and the ammonium sulfate is combined with the amorphous iron phosphate. After the amorphous iron phosphate is crystallized into the monoclinic dihydrate iron phosphate, the ammonium radical ions fall off, that is, the ammonium sulfate does not play a role, and the specific surface area of the iron phosphate cannot be increased.
[0080] Ammonium sulfate is added during the synthesis of the yellow material (as shown in Comparative Example 5), and the specific surface area of the obtained iron phosphate is improved to a certain extent relative to Comparative Example 1, but the specific surface area is relatively small compared with Examples 1-6. Ammonium sulfate is added during the synthesis of the yellow material, and the amount of ammonium added during the synthesis process increases. At this time, the introduced sulfate ions will be lost along with the by-products during washing. During crystallization, since the ammonium ions have been attached to the surface of the amorphous iron phosphate, the size of the seed crystal itself will increase, and the size of the primary particles will not decrease after crystallization. After sintering, the ammonium ions will be burned and removed by the gas, and the space left will increase the specific surface area, but the degree of increase is limited.
[0081] In Examples 1 to 6, phosphoric acid is first added during crystallization, and then ammonium sulfate / ammonium dihydrogen phosphate / diammonium hydrogen phosphate is added. Phosphoric acid will first be adsorbed on the surface of amorphous particles, and then ammonium sulfate / ammonium dihydrogen phosphate / diammonium hydrogen phosphate is added to make ammonium ions and iron complex between nanoparticles. For ammonium sulfate, sulfate ions can also replace part of phosphate to reduce the iron-phosphorus ratio while reducing the aggregation between particles. During the dehydration process, sulfate and ammonium ions will be removed by the burning gas, and the space left will increase the specific surface area of ferric phosphate, and the positive gas pressure can play a role in pore formation, reducing the aggregation between particles, thereby obtaining iron phosphate with small primary particles, uniform particle distribution, and high specific surface area.
[0082] Example 7 (1) Ingredients: Weigh 68.03 g of diammonium hydrogen phosphate into a beaker, add 159.88 g of water, stir to dissolve, and prepare a diammonium phosphate solution with a phosphorus content of 7%; weigh 700 g of ferrous sulfate solid, add 800 g of deionized water, stir for 10 min to pre-dissolve, then add 5% of the total weight of the system concentrated sulfuric acid to prepare a solution with an iron concentration of about 7%, and then add 43.27 g of 25% concentration hydrogen peroxide for oxidation to obtain a ferric sulfate solution.
[0083] (2) Synthesis: Add 50g of water as the base liquid to the flask, start rapid stirring, and the stirring frequency is 1200r / min. Add ferric sulfate solution, diammonium phosphate solution and ammonia water to the flask in parallel through a peristaltic pump, control the feeding time to be 30min, the synthesis temperature to be 35℃, the pH value to be 1.9, and then continue to stir and react for 30min; after the reaction is completed, a yellow material is obtained. The yellow material is subjected to filter pressing treatment, and the solid phase is washed to obtain the washed yellow material.
[0084] (3) Crystallization: Add water to the washed yellow material to make a slurry and disperse it. Add the dispersed slurry into a flask and start rapid stirring at a frequency of 1200 r / min. Add 5.19 g of phosphoric acid and raise the temperature to 70°C. Continue stirring for 15 min, take a sample to measure the pH value and record it. Control the pH value within the range of 1.3-1.8. Then add ammonium sulfate in an amount 0.01 times the molar amount of iron in the slurry, raise the temperature to 90°C, continue stirring. After the slurry turns white, adjust the stirring frequency to 500 r / min and continue to keep warm for 3 hours. The reaction is then completed.
[0085] (4) Filter the aged slurry, and wash the filter cake twice with 750 g of water; dry the filter cake in an oven at 120° C. for 9 h to obtain ferric phosphate dihydrate; dehydrate the prepared ferric phosphate dihydrate in a muffle furnace at 540° C. for 3 h to obtain anhydrous ferric phosphate.
[0086] Example 8 (1) Ingredients: Weigh 59.26 g of monoammonium phosphate into a beaker, add 260 g of water, stir to dissolve, and prepare a monoammonium phosphate solution with a phosphorus content of 5%; weigh 700 g of ferrous sulfate solid, add 800 g of deionized water, stir for 10 min to pre-dissolve, then add 5% of the total weight of concentrated sulfuric acid to prepare a solution with an iron concentration of about 7%, and then add 43.27 g of 25% concentration hydrogen peroxide to oxidize to obtain a ferric sulfate solution.
[0087] (2) Synthesis: Add 50g of water as the base liquid to the flask, start rapid stirring, and the stirring frequency is 1200r / min. Add ferric sulfate solution, monoammonium phosphate solution and ammonia water to the flask in parallel through a peristaltic pump, control the feeding time to be 30min, the synthesis temperature to be 30℃, the pH value to be 2.0, and then continue to stir and react for 30min; after the reaction is completed, a yellow material is obtained. The yellow material is subjected to filter pressing treatment, and the solid phase is washed to obtain the washed yellow material.
[0088] (3) Crystallization: Add water to the washed yellow material to make a slurry and disperse it. Add the dispersed slurry into a flask and start rapid stirring at a frequency of 1200 r / min. Add 5.19 g of phosphoric acid and raise the temperature to 80°C. Continue stirring for 15 min, take a sample to measure the pH value and record it. Control the pH value within the range of 1.3-1.8. Then add ammonium sulfate in an amount 0.01 times the molar amount of iron in the slurry, raise the temperature to 95°C, continue stirring. After the slurry turns white, adjust the stirring frequency to 500 r / min and continue to keep warm for 3 hours. The reaction is then completed.
[0089] (4) Filter the aged slurry, add 1000 g of water to the cake and wash it twice; dry the filter cake in an oven at 100° C. for 12 h to obtain dihydrated iron phosphate; dehydrate the prepared dihydrated iron phosphate in a muffle furnace at 560° C. for 2.5 h to obtain anhydrous iron phosphate.
[0090] Example 9 (1) Ingredients: Weigh 118.52 g of monoammonium phosphate into a beaker, add 332.82 g of water, stir to dissolve, and prepare a monoammonium phosphate solution with a phosphorus content of 7%; weigh 1400 g of ferrous sulfate solid, add 2240 g of deionized water, stir for 10 min to pre-dissolve, then add 9% of the total weight of the system concentrated sulfuric acid to prepare a solution with an iron concentration of about 6%, and then add 86.54 g of 25% concentration hydrogen peroxide for oxidation to obtain a ferric sulfate solution.
[0091] (2) Synthesis: Add 100g of water as the base liquid to the flask, start rapid stirring, and the stirring frequency is 1200r / min. Add ferric sulfate solution, monoammonium phosphate solution and ammonia water to the flask in parallel through a peristaltic pump, control the feeding time to be 30min, the synthesis temperature to be 50℃, the pH value to be 1.7, and then continue to stir and react for 45min; after the reaction is completed, a yellow material is obtained. The yellow material is subjected to filter pressing treatment, and the solid phase is washed to obtain the washed yellow material.
[0092] (3) Crystallization: Add water to the washed yellow material to make a slurry and disperse it. Add the dispersed slurry into a flask and start rapid stirring at a frequency of 1200 r / min. Add 10.38 g of phosphoric acid and raise the temperature to 85°C. Continue stirring for 15 min, take a sample to measure the pH value and record it. Control the pH value within the range of 1.3-1.8. Then add ammonium sulfate in an amount 0.01 times the molar amount of iron in the slurry, raise the temperature to 90°C, continue stirring. After the slurry turns white, adjust the stirring frequency to 500 r / min and continue to keep warm for 3 hours. The reaction is then completed.
[0093] (4) The aged slurry was filtered, and the cake was washed twice with 1200 g of water; the filter cake was placed in an oven and dried at 90°C for 12 h to obtain dihydrated iron phosphate; the prepared dihydrated iron phosphate was placed in a muffle furnace and dehydrated at 570°C for 2 h to obtain anhydrous iron phosphate.
[0094] Example 10 (1) Ingredients: Weigh 50.48 g of phosphoric acid into a beaker, add 177.41 g of water, stir to dissolve, and prepare a monoammonium phosphate solution with a phosphorus content of 7%; weigh 89.92 g of ferrous nitrate solid, add 420 g of deionized water, stir for 10 min to pre-dissolve, then add 5% of the total weight of the system concentrated sulfuric acid to prepare a solution with an iron concentration of about 5%, and then add 43.27 g of 25% concentration hydrogen peroxide for oxidation to obtain a ferric sulfate solution.
[0095] (2) Synthesis: Add 50g of water as the base liquid to the flask, start rapid stirring, and the stirring frequency is 1200r / min. Add ferric nitrate solution, phosphoric acid solution and ammonia water to the flask in parallel through a peristaltic pump, control the feeding time to be 30min, the synthesis temperature to be 55℃, the pH value to be 1.6, and then continue to stir and react for 30min; after the reaction is completed, a yellow material is obtained. The yellow material is subjected to filter pressing treatment, and the solid phase is washed to obtain the washed yellow material.
[0096] (3) Crystallization: Add water to the washed yellow material to make a slurry and disperse it. Add the dispersed slurry into a flask and start rapid stirring at a frequency of 1200 r / min. Add 5.91 g of phosphoric acid and raise the temperature to 75°C. Continue stirring for 15 min, take a sample to measure the pH value and record it. Control the pH at 1.6. Then add ammonium sulfate 0.015 times the molar amount of iron in the slurry, raise the temperature to 85°C, continue stirring. After the slurry turns white, adjust the stirring frequency to 500 r / min, continue to keep warm and age for 2 hours, and the reaction is completed.
[0097] (4) Filter the aged slurry, add 1000 g of water to the cake and wash it twice; dry the filter cake in an oven at 130° C. for 12 h to obtain ferric phosphate dihydrate; dehydrate the prepared ferric phosphate dihydrate in a muffle furnace at 550° C. for 3 h to obtain anhydrous ferric phosphate.
[0098] Figure 12-15 They are SEM images of the iron phosphate obtained in Examples 7 to 10 respectively.
[0099] The relevant physical and chemical indicators of the iron phosphate of Examples 7 to 10 are shown in Table 2.
[0100] Table 2 The iron phosphate obtained in Examples 1 to 10 and Comparative Examples 1 to 5 was respectively used to prepare lithium iron phosphate materials in the following manner: (1) Weigh appropriate amounts of iron phosphate, lithium carbonate, glucose and PEG-2000 powder and add them into a sand mill. The molar ratio of iron phosphate to lithium carbonate is 1:1.029. The masses of glucose and PEG-2000 are 8.5% and 2% of the mass of iron phosphate, respectively.
[0101] (2) Add appropriate amount of deionized water and control the solid content to 50% for sand grinding. The sand grinding parameters are 2200 rpm for 3 hours.
[0102] (3) The sand-milled slurry was spray-dried, and the spray-dried powder was placed in a box furnace and sintered at 760° C. for 8 hours under a nitrogen atmosphere to obtain lithium iron phosphate powder.
[0103] The lithium iron phosphate materials obtained above are assembled into batteries in the following ways: (1) The prepared lithium iron phosphate powder, PVDF and conductive carbon were added into a homogenizer at a mass ratio of 8:1:1, and an appropriate amount of polyvinyl pyrrolidone was added for homogenization.
[0104] (2) Apply the homogenized slurry evenly onto aluminum foil using a spatula and dry it in a vacuum oven overnight.
[0105] (3) The dried material is sliced into positive electrode sheets using a slicer, and weighed to calculate the loading amount of the active substance. The positive electrode shell, positive electrode sheet, UBE separator, lithium sheet, gasket, spring and negative electrode shell are assembled in sequence, and an appropriate amount of TC-E201 electrolyte is dripped into them, and the button cells required for the test are obtained by pressing and packaging in a tablet press.
[0106] The button cells assembled separately were placed in a battery testing system for battery performance testing. The test voltage range was 2.5V~3.75V, the test temperature was room temperature, and the charge and discharge capacities were tested at 0.2C, 0.5C, 1C, 2C, and 5C.
[0107] The performance of button-type batteries assembled with lithium iron phosphate prepared from the iron phosphate obtained in Examples 1 to 8 and Comparative Examples 1 to 5 is shown in Table 3. It can be seen that the lithium iron phosphate prepared from the iron phosphate obtained by the pre-crystallization and crystallization process of the present invention can improve the discharge capacity and rate performance of the battery.
[0108] Table 3 The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high specific surface area iron phosphate, characterized in that: The specific surface area of the iron phosphate is greater than 8.5 m 2 / g, the primary particle size is 50~150nm, and the secondary particles are in the shape of sticky rods or flakes.
2. The high specific surface area iron phosphate according to claim 1, characterized in that: The crystallinity of the ferric phosphate is 60-90%.
3. A method for preparing iron phosphate with high specific surface area, characterized in that: include: The phosphorus source solution and the iron source solution are mixed to react and obtain an amorphous iron phosphate slurry; performing solid-liquid separation on the amorphous ferric phosphate slurry to obtain amorphous ferric phosphate; In the slurry prepared by re-slurrying amorphous iron phosphate and water, an inorganic acid is first added to perform pre-crystallization, and then an ammonium salt is added to perform crystallization; The crystallized slurry is subjected to solid-liquid separation treatment, and the obtained solid phase is subjected to washing, drying and dehydration treatment to obtain iron phosphate with a high specific surface area.
4. The method for preparing ferric phosphate with high specific surface area according to claim 3, characterized in that: The phosphorus source is at least one of phosphoric acid, monoammonium phosphate, diammonium phosphate, and diammonium hydrogen phosphate; the iron source is at least one of ferrous sulfate, ferrous nitrate, iron powder, ferric chloride, and ferric oxide; the inorganic acid is one or both of phosphoric acid and sulfuric acid; and the ammonium salt is at least one of ammonium sulfate, diammonium phosphate, and diammonium hydrogen phosphate.
5. The method for preparing ferric phosphate with high specific surface area according to claim 3, characterized in that: The reaction temperature is 25-65° C., and the pH value is 1.4-2.
2.
6. The method for preparing ferric phosphate with high specific surface area according to claim 3, characterized in that: Inorganic acid is added to the re-slurry of amorphous iron phosphate and water to adjust the pH value of the system to 1.3-1.8; after adding the inorganic acid, the system is heated to 65° C.-85° C. for pre-crystallization.
7. The method for preparing ferric phosphate with high specific surface area according to claim 3, characterized in that: The ammonium salt is ammonium sulfate; the amount of ammonium sulfate added is determined according to the molar ratio of iron in the slurry prepared by re-slurrying ammonium sulfate with amorphous iron phosphate and water being 0.01-0.1:
1.
8. The method for preparing ferric phosphate with high specific surface area according to claim 3 or 7, characterized in that: The temperature for crystallization by adding ammonium salt is higher than the temperature for pre-crystallization but not more than 100°C.
9. A lithium iron phosphate, characterized in that: The product is prepared by using the high specific surface area iron phosphate described in claim 1 or 2 or the iron phosphate prepared by the preparation method described in any one of claims 3 to 8 as a precursor.
10. A battery, characterized in that: Including the lithium iron phosphate as described in claim 9.
Citation Information
Patent Citations
Preparation method of battery grade iron phosphate with low impurity, high iron-phosphorus ratio and large specific surface
CN108455547A
Layered nanoscale iron phosphate as well as preparation method and application thereof
CN116902944A
Lithium iron phosphate material and preparation method thereof, positive pole piece and secondary battery
CN117525336A
Anhydrous iron phosphate and preparation method thereof
CN117602602A
Iron phosphate with large specific surface area and high tap density, preparation method of iron phosphate, positive electrode material, positive electrode plate and battery
CN117699766A
Cited By
Iron phosphate precursor as well as preparation method and application thereof
CN120736494A
Iron phosphate precursor, method for preparing the same and use thereof
CN120736494B